Long-term forecasting technology of macroeconomic systems development: regional aspect - Grinchenko, Marina; Cherednichenko, Olga; Babych, Igor (Springer-Verlag GmbH, 2013)
Conducting of effective public policy is impossible without the scientifically substantiated evaluation of taken decisions. Long-term modeling and forecasting is the tool that allows evaluating the impact of the ongoing reforms on macroeconomic systems’ development. This requires the processing of huge amount of diverse information. This article is devoted to modeling and long-term forecasting of regional macroeconomic systems’ development. The simulation model based on the method of system dynamics is proposed. The generalized forecasting technology, which includes simulation model setup, validation and long-term forecasting, is developed. The numerical experiments and the forecast of Kharkiv region development until 2025 were carried out on the basis of the suggested information technology.
Keywords: forecasting; information technology; region; development